Guatemala : 2022 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report, 2022)
The remarkable resilience of the economy during the pandemic, driven by policy support, favorable credit conditions and a favorable external environment, has almost returned the level of GDP to its pre-pandemic projected trend. Reflecting the prevalence of domestic factors, headline inflation eased to 3 percent (the lower limit of the inflation target band) at end-2021. For 2022, growth is expected to moderate while inflation is expected to rise in line with global inflationary pressures. Despite the resilience, social indicators such as poverty and malnutrition remain high. The outlook is very uncertain with significant downside risks, mostly external, including from the pandemic, geopolitical tensions, and the tightening of global financial conditions in response to global inflationary pressures.